Evaluation of user emotion while listening music using physiology measurement: skin conductance / Nurazimah Basri - Basri, Nurazimah (2014)
Physiological signals for emotion are very well known among physiologists. It is being explored in order to recognize the people's emotion. However, little attention has been paid so far to this matter compared to audio-visual emotion channels such as speech or facial expression. Therefore, the purpose of this study is to analyze the user's emotion by adopting physiological measurement. There are three types of methods that have been used in this study which is verbal (interview), non-verbal (questionnaire) and physiological data. For collecting physiological data, four songs have been chosen and skin conductance is used as physiological measurement. The skin conductance is measured by attaching the device to the participants' fingers and the graphs will be produced. From the results, it shows that the main types of emotions have been produced while listening to all types of song such as disappointment (sad), pleasant surprise, bored and calm. These results are supported by questionnaires and interviews. Besides that, the graph of skin conductance also shows the number of peaks and graph pattern among participants. As a result, the findings of this study provide empirical evidence that physiological measurement able to detect one's emotion and the findings also can be used in Human Computer Interaction (HCI) areas also for further research in the future.